End-to-End Message Exchange in a Deployable Marine Environment Hierarchical Wireless Sensor Network - César Ortega-Corral; Luis E. Palafox; J. Antonio García-Macías; Jaime Sánchez-García; Leocundo Aguilar (International Journal of Distributed Sensor Networks)
We present a pragmatic view of different approaches used to guarantee data delivery in a deployable marine habitat monitoring system, composed of a two-tier dual frequency (2.4 GHz/900 MHz) hierarchical wireless sensor network (WSN). We cover end-to-end application layer aspects. At the lower tier, we preconfigured endpoint (EP) transceivers for automatic data acquisition and wireless transfer using their native Application Program Interface (API) framework. These endpoints communicate with a more powerful intermediate cluster-head (CLH) system. At the upper tier, we deployed a modified low level 8-bit “Lighter” version of the well-known web application protocol called JavaScript Object Notation (JSON, or in our case LJSON) for back and forth CLH to BS validated message exchange. These LJSON messages are converted by the BS to 16-bit JSON and vice versa, for remote Internet interaction. And finally, the BS software establishes Internet Protocol (IP) client socket connections with a remote custom JSON service, in charge of marine habitat sensor data reception, verification, and nonvolatile database storage.